1980
DOI: 10.1128/aem.40.2.217-222.1980
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature and Retention Time on Methane Production from Beef Cattle Waste

Abstract: The effect of temperature and retention time on the rate of methane production from waste of beef cattle fed a finishing diet was investigated by using continuously mixed 3-liter working volume anaerobic fermentors. The temperatures ranged from 30 to 65�C with 5�C increments between fermentors. The fermentors were fed once per day with 6% volatile solids (organic matter). Retention time for each temperature was varied from 18 to 2.5 days. After 3-volume turnovers, samples were obtained on 4 consecutive days. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
28
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(35 citation statements)
references
References 8 publications
6
28
0
1
Order By: Relevance
“…In the one-phase reactor, the biogas production increased by 56% on increasing the temperature from 25 to 358C. The results obtained are in agreement with previous results, which showed an improvement in biogas yields with increasing temperature [21,22]. In the mesophilic temperature range (25 -358C), higher temperatures tend to give better methane yields.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…In the one-phase reactor, the biogas production increased by 56% on increasing the temperature from 25 to 358C. The results obtained are in agreement with previous results, which showed an improvement in biogas yields with increasing temperature [21,22]. In the mesophilic temperature range (25 -358C), higher temperatures tend to give better methane yields.…”
Section: Resultssupporting
confidence: 90%
“…These three reactors produced similar percentages of CO2 and N2. R22 (25) did not provide similar results since its biogas production efficiency was significantly lower than the other reactors. It typically contained 40 to 45% CH4, 30 to 35% CO2, and 25 to 30% N2.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…However, this may reflect the utilization of SCFAs and BCFAs for methanogenesis. Varel et al (1980) reported that VFAs can be used as substrate for methanogenesis. This drop in VFA concentration at Day 21 is reflected in the overall pH values at Day 21 (Table 2).…”
Section: Total Branched-chain Fatty Acids and Straight-chain Fatty Acidsmentioning
confidence: 99%